Criteria for indication and treatment modification in a cohort of patients with prostate cancer treated with hormone therapy. Issue 12 (December 2018) - Lebret, Thierry; Ruffion, Alain; Latorzeff, Igor; Zerbib, Marc; Moreau, Jean-Luc; Rossi, Dominique; Pello-Leprince-Ringuet, Nathalie; Perrot, Valérie; Hennequin, Christophe
Background: No published studies have specifically assessed whether treatment modifications to androgen deprivation therapy (ADT) for prostate cancer (PCa) are frequently carried out in routine clinical practice. The current study was conducted to determine what proportion of patients who had initiated hormone therapy with a gonadotropin-releasing hormone (GnRH) analogue then had their treatment regimen modified during the first 24 months. Methods: A prospective, noninterventional study was carried out in routine clinical practice in France. Patients with locally advanced or metastatic PCa were followed up for 2 years after treatment initiation with a GnRH analogue. The primary endpoint was the proportion of patients with a modification to their initial hormone therapy. Results: In total, 1301 patients were enrolled into the study by 204 physicians, and the primary endpoint could be evaluated for 891 patients. The GnRH analogue treatment was initiated for metastatic PCa (24.2%), locally advanced PCa without planned local treatment (20.6%), locally advanced PCa in association with radiotherapy (31.6%), and biochemical recurrence after local treatment (21.4%). Hormonal treatment was modified in 43.8% (390/891) of patients during the 24-month follow-up period after GnRH analogue initiation. In 61.3% of cases (239/390), the type of modification involved a change of GnRH analogue formulation or switch to another GnRH analogue. A total of five significant predictive factors for GnRH analogue treatment modification were identified: metastatic stage; physician sector; physician speciality; presence or absence of urinary symptoms; and intermittent versus continuous ADT. Conclusions: This study shows that in 43.8% of the patients with advanced PCa, ADT is modified in the first 2 years after initiation in routine clinical practice. Predictive factors for alteration of ADT were metastatic stage and the choice of an intermittent schedule.